1995
DOI: 10.1128/jcm.33.7.1961-1962.1995
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective case-control study of diffusely adhering Escherichia coli and clinical features in children with diarrhea

Abstract: A retrospective case-control study with a small population group revealed that, among clinical signs, vomiting but not diarrhea was significantly associated with the presence of diffusely adhering Escherichia coli (DAEC) in children suffering from gastroenteritidis (P < 0.05). Of the children carrying DAEC strains, those who were F1845 DNA probe positive had a significantly longer hospital stay than those who were F1845 DNA probe negative. We believe that the heterogeneity of DAEC strains is responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 12 publications
0
14
0
3
Order By: Relevance
“…The first DNA probe, named daaC, was generated by Stapleton et al (413) and was a 300-bp PstI fragment of plasmid pSSS1 (daa operon), coding for part of an accessory protein of F1845 adhesin expressed by the diarrheagenic Afa/Dr DAEC C1845 strain (43). This DNA probe has been used in a large majority of the epidemiological studies of the association of Afa/Dr DAEC with diarrhea and urinary tract infections (1,5,68,112,127,130,131,141,143,152,208,209,256,257,293,329,344,364,366,367,400). Another constructed DNA probe, named drb (130), was a 260-bp PstI fragment of plasmid pIL14 (afa-1 operon) coding for the AfaE-I adhesin expressed by the uropathogenic Afa/Dr DAEC KS52 strain (243).…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…The first DNA probe, named daaC, was generated by Stapleton et al (413) and was a 300-bp PstI fragment of plasmid pSSS1 (daa operon), coding for part of an accessory protein of F1845 adhesin expressed by the diarrheagenic Afa/Dr DAEC C1845 strain (43). This DNA probe has been used in a large majority of the epidemiological studies of the association of Afa/Dr DAEC with diarrhea and urinary tract infections (1,5,68,112,127,130,131,141,143,152,208,209,256,257,293,329,344,364,366,367,400). Another constructed DNA probe, named drb (130), was a 260-bp PstI fragment of plasmid pIL14 (afa-1 operon) coding for the AfaE-I adhesin expressed by the uropathogenic Afa/Dr DAEC KS52 strain (243).…”
Section: Diagnosismentioning
confidence: 99%
“…Epidemiological studies conducted by use of colony blotting with the daaC DNA probe have demonstrated an age-related incidence of Afa/Dr DAEC in diarrhea in children, which apparently begins after age 2 or 3 (112,127,141,143,152,167,208,209,256,344,364). Moreover, E. coli strains expressing Afa/Dr adhesins have been found with similar frequencies in patients with diarrhea and control subjects (127,167,356).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusely adhering E. coli (DAEC) is a newly proposed pathotype of diarrheagenic E. coli based on epidemiological studies [1]. However, the enteric pathogenicity of these strains has not yet been established, while DAEC strains have been implicated as agents of diarrhea in several studies [3][4][5][6][7][8], others have not identified DAEC as a diarrheal agent [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between Afa/Dr DAEC and diarrhea in children as a function of age has been more convincingly demonstrated in age cross-sectional studies showing an increased incidence in children Ͻ1 to 5 years of age. These studies were conducted in the United States (116), Mexico (117), and different South American countries, including Chile (118), Brazil (58,71,(119)(120)(121), Colombia (122), Peru (123)(124)(125)(126)(127), and Argentina (128), as well as in Thailand (50), Bangladesh (129), Japan (119), New Caledonia (45,63,130), various places in Africa (131)(132)(133), and European countries, includ-ing the United Kingdom (134) and France (135,136). In Afa/Dr DAEC strains isolated from stools of children, the sat gene has been found in almost half of the diarrhea-associated Afa/DrDAEC strains and was not present in all the non-diarrhea-associated Afa/ DrDAEC strains (137).…”
Section: Diarrheamentioning
confidence: 99%